Simplification of Dialogues in Shakespeare’s Drama : Macbeth - Nada Zahro Afifah; Sunardi; A.K Amarullah (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2020)
The purposes of this study are to find the simplification language usage, the vocabulary and structure, and content in unabridged and abridged dialogues of Shakespeare’s Drama: Macbeth. This research used descriptive qualitative research and the script of drama to analyze the dialogue of each character and the language simplification usage, the vocabulary and structure controlled in unabridged and abridged, and the content in abridged version.. The data source that used in this research is a dialogue of Shakespeare’s drama Macbeth in unabridged and abridged version. The result of the reasearch showed that there were simplification of vocabulary, structure and content. Simplification of vocabulary and structure occured inside the language rules while simplification of content occured inside the dialogue content. All the simplification language occured because of the verbs, the length of discursive segments, and the elements of drama